Population shift between the open and closed states changes the water permeability of an aquaporin Z mutant - Xin, Lin (2013)
Aquaporins are tetrameric transmembrane channels permeable to water and other small solutes. Wild-type (WT) and mutant Aquaporin Z (AqpZ) have been widely studied and multiple factors have been found to affect their water permeability. In this study, molecular dynamics simulations have been performed for the tetrameric AqpZ F43W/H174G/T183F mutant. It displayed 10% average water permeability compared to WT AqpZ, which had been attributed to the increased channel lumen hydrophobicity. Our simulations, however, show a ring stacking between W43 and F183 acting as a secondary steric gate in the triple mutant with R189 as the primary steric gate in both mutant and WT AqpZ. The double gates (R189 and W43-F183) result in a high population of the closed conformation in the mutant. Occasionally an open state, with diffusive water permeability very close to that of WT AqpZ, was observed. Taken together, our results show that the double-gate mechanism is sufficient to explain the reduced water permeability in the mutant without invoking effects arising from increased hydrophobicity of the channel lumen. Our findings provide insights into how aquaporin-mediated water transport can be modulated and may further point to how aquaporin function can be optimized for biomimetic membrane applications.